Pemanfaatan Tumbuhan Arecaceae (Palem-Paleman) Oleh Masyarakat Dayak Randu' Di Desa Batu Buil Kecamatan Belimbing Kabupaten Melawi - Irwan Lovadi, Santi Nuryanti, Riza Linda (Jurnal Protobiont, 2015)
Several Arecaceae plant are widely used by the local resident in Batu Buil village, especially coconuts, sugar palms, areca nuts, nipah, oil palms and sago. The aims of this study were todetermine the species of each Arecaceae plant, their useful parts and how were they used by Dayak Randu’ tribe in Batu Buil village. This study was conducted from December 2013 until February 2014. Data were gathered by interviewing the respondents using the snowball method. Arecaceae were used by Dayak Randu’ tribe in different ways, such as plaited, shredded, dried and boiled. Leaves, stems, fruits and flowers were frequently used, while roots and seeds were rarely used. Result showed that there were 7 species of Arecaceae which commonly used as food source, traditional medicine, building materials, handicrafts, and others.